Proposed Marketing Strategy to Increase Visitation Level of the International Sharia Economic Festival (ISEF) Event of Bank Indonesia - Putri Zayyana, Syavika; Furinto, Asnan (Fakultas Ekonomi Universitas Gresik, 2023)
The sharia economy has gained traction in Indonesia, and Bank Indonesia has been promoting this sector through various strategies, including the Indonesia Sharia Economic Festival (ISEF) event. However, ISEF has faced stagnant visitation levels in recent years. This study examines the marketing strategies used by Bank Indonesia to address this issue. A literature review provides insights into the sharia economy's concept, growth in Indonesia, and ISEF's visitor challenges. Bank Indonesia's marketing strategies for ISEF, such as social media and industry community collaborations, are analyzed qualitatively and quantitatively. The effectiveness of these strategies in addressing stagnant visitation levels is assessed using SWOT analysis and TOWS matrix. The study proposes marketing strategies, such as a new STP and strengthening customer engagement strategies, to attract visitors to ISEF. This study contributes to the understanding of marketing strategies for promoting the sharia economy in Indonesia